Avicultura industrial do Oeste paranaense: barreiras não-tarifárias e estratégias competitivas - Cruz, Anyelly Cristina (2019)
Brazil is considered one of the largest and most successful exporters in the world of poultry meat, having taken the top position in the exporters' ranking (4.32 million tons) in 2017. Among the exporting states, there is Paraná, which exported 37.20% of the country's total chicken meat in the same year. However, the chicken meat market is increasingly complex and competitive due to the growing world demand, the perishability of the product and the requirements for hygienic-sanitary controls. Parallel to these concerns are commercial barriers (tariff and non-tariff) that hinder competition in important markets. Once the importance of the sector is demonstrated, the objective of this study is to analyse how the poultry industry of the west of Paraná adapts to the non-tariff barriers of the international market. For this, this research is characterized as qualitative, of the exploratory type, which adopts as strategy of delineation the multicase and descriptive analysis. The primary data were collected through a semistructured interview with specialists and managers of exports of the main poultry industries of the Western region of Paraná. Secondary data were obtained through documents from various government agencies, as well as websites, annual reports and articles on agribusiness and livestock. For analysis, the Pareto principle was used to identify which barriers most influence the performance of exports. Finally, the descriptive analysis was based on all the theoretical material raised in the referential of this study and in the interviews, in order to identify the non-tariff barriers and to discuss how they influence the competitive strategies of the industrial poultry industry in Paraná. As a conclusion, it was found that agroindustrial product is a matter of food security, in which the state needs to intervene and negotiate with other governments so that the intra-firm acquired competitive advantages are maintained and not erased by trade barriers and exchange rate variations.